PENGARUH SOLUTION TREATMENT DAN MEDIA PENDINGIN PADA PROSES HOT ROLLING TERHADAP KEKUATAN BAJA MANGAN AUSTENITIK - Nadya Salsabila Frendyta; Arif Tjahjono; Permana Andi Paristiawan (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
A steel with high hardness but relatively low ductility and toughness is called austenitic manganese steel. This steel implementation often suffers from defect and failure. Responding to this problem, the study was done by manipulating a heat treatment process in order to change the microstructure, refine the grain, and improve its mechanical properties thereby increasing its ductility and toughness. It was begun by heating the austenitic manganese steel to austenizing temperature (1000°C) and holding for 100 minutes. The solution treatment process is carried out by a hot rolling process with a temperature of 1100 °C. Quenching process is done using water cooler and ice water as media. Temperature variation selection aimed to find out the phase change in microstructure and its effect on mechanical properties. In solution treatment process with water cooling, austenitic manganese steel indicated a significant microstructure with little martensite and more dominant in austenite and ferrite microstructure. This phenomenon gave the hardness reduction effect which in turn indicated the increase of ductility and toughness on austenitic manganese steel with high tensile and elongation test result. Therefore, austenitic manganese steel which is the result of a solution treatment process with water cooling will have a better lifetime in its implementation in industrial world.